Platelet activation and arterial peripheral serotonin turnover in cardiac remodeling associated to aortic stenosis. Issue 1 (January 2015) - Rouzaud‐Laborde, Charlotte; Delmas, Clément; Pizzinat, Nathalie; Tortosa, Florence; Garcia, Cédric; Mialet‐Perez, Jeanne; Payrastre, Bernard; Sié, Pierre; Spreux‐Varoquaux, Odile; Sallerin, Brigitte; Carrié, Didier; Galinier, Michel; et al.
<x xml:space="preserve">Abstract</x> Peripheral serotonin (5‐HT) has been involved in adverse cardiac remodeling and valve fibrosis. The peripheral levels of 5‐HT mainly depend on its release from activated platelets and degradation by monoamine oxidase A (MAO‐A). The SERAOPI study investigated the relationship between arterial serotoninergic system, degree of platelet activation and cardiac remodeling, in patients with aortic valve stenosis (AS). Thirty patients with severe AS and 15 control subjects underwent transthoracic echocardiography, radial, and aortic arterial blood sampling. Measurements of 5‐HT and its MAO‐A‐dependent degradation product, 5‐HIAA, were performed by HPLC. Arterial platelet activation was assessed by flow cytometry analysis of platelet surface expression of P‐selectin and activated integrin GPIIb/IIIa. Activated platelets and arterial plasma 5‐HT increased in AS patients as compared to control subjects (P‐selectin 1.08 ± 0.2MFI vs. 0.49 ± 0.1MFI, P = 0.04; GPIIb/IIIa 0.71 ± 0.1MFI vs. 0.35 ± 0.1MFI; P = 0.0015 and arterial plasma 5‐HT 11.55 ± 1.6 nM vs. 6.18 ± 0.7 nM, P = 0.028, respectively). Moreover, 5‐HT was strongly correlated to left ventricular hypertrophy assessed by echocardiography. The correlation was independent of cardiovascular risk comorbidities and others echocardiographic AS parameters. Finally, plasma 5‐HIAA increased in AS patients (74.64 ± 9.7 nM vs. 37.16 ± 4.1 nM; P = 0.0002) indicating a higher 5‐HT degradation rate by MAO‐A. Platelet activation, arterial circulating serotonin, and serotonin degradation increased in patients with AS. These observations suggest that the serotoninergic system may contribute to the pathogenesis of AS including valve fibrosis and adverse ventricular remodeling. Am. J. Hematol. 90:15–19, 2015. © 2014 Wiley Periodicals, Inc.